2018
DOI: 10.1093/cercor/bhy174
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Network Oscillations Rescue Memory Consolidation Deficits Caused by Sleep Loss

Abstract: Oscillations in the hippocampal network during sleep are proposed to play a role in memory storage by patterning neuronal ensemble activity. Here we show that following single-trial fear learning, sleep deprivation (which impairs memory consolidation) disrupts coherent firing rhythms in hippocampal area CA1. State-targeted optogenetic inhibition of CA1 parvalbumin-expressing (PV+) interneurons during postlearning NREM sleep, but not REM sleep or wake, disrupts contextual fear memory (CFM) consolidation in a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(164 citation statements)
references
References 77 publications
(166 reference statements)
16
148
0
Order By: Relevance
“…Our findings are further supported by studies that found that targeting and activation of parvalbumin interneurons at specific stimulation frequencies could ameliorate spatial learning deficits. For example, rhythmic PV interneuron activation in the hippocampal CA1 in sleep‐deprived animals during non‐REM sleep improved performance in memory tasks . Because seizures in IHKA mice can occur during all brain states, with a majority (~90%) arising from a non‐theta state, animals in our present study likely received some light activation of PV interneurons during non‐REM sleep at a theta frequency (~7 Hz) similar to that used in the described study .…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Our findings are further supported by studies that found that targeting and activation of parvalbumin interneurons at specific stimulation frequencies could ameliorate spatial learning deficits. For example, rhythmic PV interneuron activation in the hippocampal CA1 in sleep‐deprived animals during non‐REM sleep improved performance in memory tasks . Because seizures in IHKA mice can occur during all brain states, with a majority (~90%) arising from a non‐theta state, animals in our present study likely received some light activation of PV interneurons during non‐REM sleep at a theta frequency (~7 Hz) similar to that used in the described study .…”
Section: Discussionmentioning
confidence: 74%
“…For example, rhythmic PV interneuron activation in the hippocampal CA1 in sleep-deprived animals during non-REM sleep improved performance in memory tasks. 33 Because seizures in IHKA mice can occur during all brain states, with a majority (~90%) arising from a non-theta state, 34 animals in our present study likely received some light activation of PV interneurons during non-REM sleep at a theta frequency (~7 Hz) similar to that used in the described study. 33 Rhythmic activation of PV interneurons has been shown to have therapeutic effects in the gamma frequency as well.…”
Section: Pv Interneuron Stimulation and Improved Cognitionmentioning
confidence: 83%
See 3 more Smart Citations